Comparison of Nonshivering Thermogenesis Induced by Norepinephrine Stress in Tree Shrews - Zhu, Wan-long; Zhang, Di; Zheng, Jia; ZHang, Lin; Liu, Jin-hu; Cheng, Jin; Wang, Zheng-kun (Journal of stress physiology & biochemistry, 2013)
(2) NE(mg/kg) = 3.3W-0.458 and (3) NE(mg/kg)= 6.6W-0.458. In the present study , we used tree shrews (Tupaia belangeri) as experiment subjects to test the effects of the three dosages of NE on NST. Results showed that all the three dosages of NE could induce the maximum NST for T. belangeri. No significant differences were found in NST among groups and the NST was respectively 2.63±0.12 (formula 1), 2.66±0. 11 (formula 2) and 2.78±0.15 (formula 3). However, when injected with NE dosage from formula 3, the increase of body temperatures was significantly higher than the other two NE dosages (increased 1.5±0. 1 oC (formula 3), 0.8±0. 2 oC (formula 2), and 0.6±0. 1 oC (formula 1), respectively). In order to prevent the death because of hyperthermia, formula 1 or 2 is recommended to be used. Nonshivering thermogenesis (NST)is an important thermogenic mechanism for small mammals. Quantitative measurement of NST is usually stimulated by injection of norepinephrine. The injection dosage of norepinephrine (NE) is critical for eliciting the maximum NST. Three empirical equations of NE dosages were often referenced in previous studies: (1) NE (mg / kg)= 2.53W-0.4